THE EFFECT OF REWARDS AND ORGANIZATIONAL CLIMATE ON THE PERFORMANCE OF PT TASMA PUJA KAMPAR EMPLOYEES - Sahlan Sahlan; Okta Dwi N; Amos Amos (PENANOMICS: International Journal of Economics, 2022)
This research was conducted to determine the effect of rewards and organizational climate on the performance of employees of PT Tasma Puja Kampar. The population in this study were employees at PT Tasma Puja Kampar, amounting to 110 people. The sample uses the slovin formula with the limit used is 5% so that the research sample is 87 employees. The data collection technique that the author uses is a questionnaire. Furthermore, the authors analyze the data using analytical and quantitative methods, the results of the study will be analyzed using multiple linear regression using the SPSS version 20.00 computer program. Based on the results of the study, it can be seen that awards and organizational climate have a significant effect on employee performance at PT Tasma Puja Kampar, with a positive regression coefficient, meaning that if rewards increase and organizational climate increases, performance will increase. Based on the calculation results show the value of R2 (coefficient of determination) or Adjusted R Square of 0.536 or 53.6%. This means that the independent variables, namely rewards and organizational climate, have a contribution of 53.6% to the dependent variable, namely performance. while the remaining 46.4% can be used by other researchers for the perfection of this study.